Penyelesaian Konflik Penguasaan Lahan dalam Kawasan Hutan Berdasarkan Skema Tora : Studi Kasus : Desa Bontula Kabupaten Gorontalo - Yusfriandi Dwi Ariesna; Dewi Wahyuni K. Baderan; Fitryane Lihawa (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
This study aims to analyze land tenure conflicts in Bontula Village, Gorontalo Regency, and evaluate the implementation of the Land Reform Object (TORA) scheme in resolving these conflicts. The conflict arises from overlapping land ownership claims between local communities and the government, often exacerbated by a lack of socialization and policy transparency. A qualitative approach was used, with in-depth interviews, participatory observation, and document analysis. Data was collected from 30 respondents, including local communities, village officials, and stakeholders such as the BPN and KLHK. The findings show that most of the Bontula community is unaware of the TORA scheme, leading to difficulties in claiming land rights. Although the TORA scheme has the potential to improve community welfare through land legalization, its implementation faces challenges due to inadequate coordination and transparency. The study recommends increased socialization, transparency, and active community participation in TORA implementation to reduce conflicts and achieve the desired outcomes.